2003
DOI: 10.1086/374276
|View full text |Cite
|
Sign up to set email alerts
|

Do Panther Chameleons Bask to Regulate Endogenous Vitamin D3Production?

Abstract: Basking by ectothermic vertebrates is thought to have evolved for thermoregulation. However, another beneficial effect of sunlight exposure, specifically the ultraviolet B (UV-B) component, includes endogenous production of vitamin D(3). In the laboratory, panther chameleons exhibited a positive phototaxis to greater visible, ultraviolet A (UV-A) and UV-B light. However, with equivalent high irradiances of UV-A or UV-B, their response to UV-B was significantly greater than it was to UV-A. Exposure of in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 37 publications
(39 reference statements)
2
39
0
Order By: Relevance
“…Studies have shown that some lizards are capable of precisely regulating their exposure to UVB Karsten et al, 2009]. Ferguson et al [2003] showed that panther chameleons exposed to UVB gradients, that were not linked to thermal gradients and were generated using artificial fluorescent lamps in the laboratory, can regulate UVB exposure independently from temperature regulation. Nevertheless, lizards in the field readily seek refuge from the sun, which is a strong UVB and heat source, when their thermal requirements are satisfied (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that some lizards are capable of precisely regulating their exposure to UVB Karsten et al, 2009]. Ferguson et al [2003] showed that panther chameleons exposed to UVB gradients, that were not linked to thermal gradients and were generated using artificial fluorescent lamps in the laboratory, can regulate UVB exposure independently from temperature regulation. Nevertheless, lizards in the field readily seek refuge from the sun, which is a strong UVB and heat source, when their thermal requirements are satisfied (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…While one species, the panther chameleon, has been shown to do this with great precision Ferguson et al, 2003;Karsten et al, 2009] and other species may have this ability [Bernard et al, 1991;Aucone et al, 2003], careful laboratory and field research is required to document this ability in other species. If a species can self-regulate its UVB exposure to maintain optimal vitamin D 3 status, then providing a suitable species-specific UVB gradient in the vivarium may be all that is necessary for this to occur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Basking behaviour for thermoregulatory purposes (Ferguson et al, 2003) is a relatively uncommon behaviour in amphibians (Hutchison and Dupré, 1992) due to their usually highly permeable skin, which allows for high rates of evaporative water loss (EWL) (Jameson, 1966;Shoemaker et al, 1992). Although some amphibians can tolerate up to 45% body water loss from evaporation alone (Shoemaker et al, 1992), water loss is thought to be a major constraining factor in many aspects of amphibian ecology (Beuchat et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…The currently available Model DMX from Spectronics Corp. (Westbury, NY), has a resolution of 10 mW/cm 2 and may not be able to adequately differentiate among irradiance levels from low wattage lamps. The older model (DM-300N), which did measure at the desired resolution, is no longer available, but literature reporting baseline data using this meter exist [Gehrmann, 1987;Ferguson et al, 2002Ferguson et al, , 2003. Most broadband radiometers tend to underestimate the actual irradiance within a band because they progressively undervalue the irradiances toward the two boundaries of the band.…”
Section: Introductionmentioning
confidence: 99%